In vitro validation of quantitative light-induced fluorescence for the diagnosis of enamel fluorosis in permanent teeth (2020)
This study aimed to validate quantitative light-induced fluorescence (QLF) as a diagnostic tool for mild and moderate enamel fluorosis in permanent teeth, comparing it to visual diagnosis and histological assessment completed using polarized light microscopy (PLM). The buccal surfaces of 139 teeth were visually classified using the Thylstrup and Fejerskov Index (TFI) into sound (TFI 0; n = 17), mild (TFI 1-2; n = 69), and moderate (TFI 3-4; n = 43) fluorosis. Fluorosis was then assessed with QLF (variables ΔF, A, and ΔQ at 5-, 15-, and 30-radiance thresholds) using as reference areas the entire surface and a region of interest (ROI), identified as the most representative region of a fluorosis lesion. PLM images of longitudinal thin sections including the ROI were assessed for histological changes. Correlations among TFI, PLM, and QLF were determined. A receiver-operating characteristic curve was conducted to determine QLF's diagnostic accuracy when compared to the TFI and PLM assessments. This was used to assess the probability that the images were correctly ranked according to severity as determined by PLM and TFI. A positive correlation was found between QLF and PLM, and between QLF and TFI. QLF showed the highest sensitivity and specificity for the diagnosis of mild fluorosis. There was also a strong agreement between TFI and PLM. The selection of a ROI resulted in a stronger correlation with TFI and PLM than when the entire surface was used. The study results indicate that defining an ROI for QLF assessments is a valid method for the diagnosis of mild and moderate enamel fluorosis.